Sistema de seguridad para un laboratorío - Calvopiña Martínez, Guillermo Xavier (2009)
In this Project an application for a security system was designed, in which computer vision and communication via Ethernet was applied. For this, Labview 8.5 Imaq vision package was used. This software allows the acquisition of images and registration numbers from student’s credentials. A template will be created to help find an area of interest which in this case is a barcode. Two cameras are used in the project, a genius Eye 110 camera with two servomotors that monitors the laboratory and a MSI StarCam camera used to extract the barcodes from student’s credentials. The sevomotors control the position of the camera. A prototype was implemented to demonstrate this application using the student’s ID cards. Additionally it is possible to monitor ambient temperature and the position of a remotely controlled camera via Ethernet.